A matter of life and death [videorecording (DVD)] - Powell, Michael, 1905-1990; Powell, Michael, 1905-1990; Powell, Michael, 1905-1990; Pressburger, Emeric, 1902-1988; Pressburger, Emeric, 1902-1988; Pressburger, Emeric, 1902-1988; Niven, David, 1910-1983; Livesey, Roger, 1906-1976; Hunter, Kim, 1922-2002 (Criterion collection, 2018)
After he survives jumping out of a burning plane and falls in love with an American radio operator, World War II British pilot Peter Carter goes on trial in heaven for a second chance at life, as he was meant to die in the crash.